AGING AND TECHNOLOGY—TURNING RESEARCH INTO REAL-WORLD IMPACT - Sixsmith, A. (Innov Aging, 2017)
AGE-WELL is a Canadian research network that aims to help older people to maintain their independence, health and social participation through accessible technologies. While these are compelling arguments for public and private investment in this area, there are still a number of key challenges in turning the research outputs into real world products and services. This talk will explore and evaluate some of these challenges and will discuss AGE-WELL’s approach to strengthen efforts in this sector.